Analysis of International Disputes Regarding Diplomatic Relations between Saudi Arabia and Qatar (Universitas Negeri Semarang, 2020)
Analysis of International Disputes Between Saudi Arabia and Qatar (Situation of Diplomatic Relations between the two countries) Abstract: Diplomatic relations by definition are relations with the mediation between representatives of two or more countries that are political in nature. In the international world, each country must have diplomatic relations with other countries, in establishing relations or interactions do not always go well, sometimes it will lead to international disputes such as those between Saudi Arabia and Qatar, as an outline of the dispute between the two countries, is caused by Saudi Arabia's view of Qatar which does not respect the gulf state's attitude, namely anti-Iran's attitude by supporting to assist Iranians and militant groups such as Muslim Brotherhood and others. The Gulf especially Arabs and made Arabs issue policies to cut off diplomatic relations with Qatar, this paper will discuss the general picture of the two countries and the history of relations between the two countries. Arabian conduct along with Qatar's response to this matter to efforts to reconcile the two countries by various parties Keywords: Diplomatic Relations, Saudi Arabia, Qatar, Disputes